Olanzapine-induced renal damages and metabolic side effects: the protective effects of thymoquinone - Bilgiç, Sedat; Korkmaz, Deniz Taştemir; Azırak, Sebile; Güvenc, Ayse Nilay; Kocaman, Nevin; Özer, Mehmet Kaya (My University, 2018)
Aim: The goal of the study is to examine the protective qualities of thymoquinone (TQ) against the side-effects of olanzapine (OLZ) in an experimental model in rat kidneys.Material and Methods: Thirty five female Spraque-Dawley rats were divided into 5 groups (n=7): Control, OLZ, OLZ+TQ-1, OLZ+TQ-2, OLZ+TQ-3. All treatments were administered for two weeks by gavage. Two weeks administration of OLZ (4 mg/kg, once a day forthe first week, 8 mg/kg once a day for the second week, p.o.) was given to all groups, except control. TQ was administered (25, 50, 100 mg/kg, once daily) by gastric tube. On treatment day 15, kidney tissues were removed for analysis.Results: TQ increased the total antioxidant status (TAS) and decreased creatinine (Cr), blood urea nitrogen (BUN), oxidative stress index (OSI) and total oxidant status (TOS) levels significantly (p<0.05).Conclusion: These results revealed that TQ improved the side-effects of OLZ, contributed to the oxygen radical scavenging activity,increased antioxidant activity and had ameliorative effects on recovery of increased serum biochemical and oxidative stress parameters. Thus, these results demonstrated that TQ had protective and antioxidant effects against adverse effects of OLZ in kidney of rats. TQ could be an effective course of therapy to enhance therapeutic efficacy
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji; Toksikoloji; Farmakoloji ve Eczacılık